Analisis Dampak Yuridis Penggabungan Akad Jual Beli dan Utang pada Transaksi Orderan Fiktif Ojek Online: (Studi Kasus Driver Gofood Di Desa Tengah, Pancur Batu) - M.Iqbal M.Iqbal (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Drivers who frequently experience fictitious orders face significant psychological impacts. Stress and frustration are common reactions when they have to face situations where they have used time and resources to respond to orders that are not taken or canceled without clear reasons. The research methodology used in this study is a qualitative approach with a case study method. The qualitative approach was chosen because it aims to understand in depth the legal impact of combining sales and purchase agreements and debts on fictitious online motorcycle taxi order transactions, especially from the perspective of online motorcycle taxi drivers. The case study method was chosen because it allows researchers to investigate in depth one particular case, namely online gofood drivers in Desa Tengah, Pancur Batu, who experienced financial losses due to fictitious orders. Based on the findings of this study, it can be concluded that fictitious orders in online motorcycle taxi services, as analyzed in the context of combining sales and purchase agreements and debts according to Islamic jurisprudence, have significant impacts both in terms of law and psychology. Legally, this practice violates the principle of a valid contract according to the fiqh of Al Masyqhul la Yusyghal, because it involves elements of fraud that are detrimental to drivers. Psychologically, drivers experience stress, frustration, and anxiety that have the potential to disrupt their overall well-being.